Optimal decision policy and budget allocation for a R&D portfolio - Costa, A.; Paixão, J.P (EURO-INFORMS 2013, 2013)
R&D portfolio management deals with the finding of the optimal decision policy for each project, that is, the determination of a sequence of actions (improvement, continuation or abandonment) made at each stage of the R&D phase that respects the allocated budget and maximizes the overall value of the portfolio. In this talk, we propose a 0-1 integer linear program for solving this problem and present computational experience allowing conclusions to be drawn on the adoption of this model. Further, we discuss the chance of incorporate additional managerial choices in the presented formulation.